Enabling learner independence and self-regulation in language education using AI tools: a systematic review - Mohebbi, Ahmadreza (Cogent education, 2025)
In this study, a systematic review was conducted to explore the role of Artificial Intelligence (AI) in language learning, drawing insights from 18 peer-reviewed articles published between 2009 and 2024. The research utilised the PRISMA framework to ensure a comprehensive, structured approach to data collection and analysis. Articles were sourced from academic databases such as Google Scholar, ERIC, and PubMed, using targeted search terms including “AI and learning speaking,” “AI and learning writing,” and “AI and improving listening.” A meticulous screening process was applied, first by title and abstract, followed by full-text analysis to ensure relevance. The studies were then subject to a dual-round thematic analysis, with each round focusing on identifying patterns and cross-validating findings related to AI’s impact on language learning outcomes. The findings of the study revealed that AI-driven tools significantly enhance language learning outcomes by promoting engagement, providing immediate feedback, and facilitating personalised learning experiences. Specific AI tools like Virtual Reality (VR) applications, automated writing feedback systems, and chatbots were analysed for their effectiveness in enhancing speaking, writing, and grammar skills. By conducting a detailed thematic analysis, this study highlighted both the benefits and limitations of AI-driven language education, underscoring AI’s role in promoting self-regulated learning while noting areas needing cautious implementation, such as over-reliance on technology and equitable access.